Mémoires d'Hadrien entre fiction et autobiographie - Osterman, Tina (Acta neophilologica, 2016)
The article is a brief analysis of the work by Marguerite Yourcenar, the famous French woman writer, the author of Memories of Hadrien, her first international success from the early 1950s. The objective of the article is to contextualize the novel into a literary sub-genre and define its formal originality within the memoir genre in the epistolary form. The mixture of the novel, memories, correspondence and poetry creates a kind of polygraphism.
Keywords: autobiographie; autobiography; avtobiografije; forme épistolaire; francoska književnost; French literature; Hadrijanovi spomini; historical novel; Literarne študije; littérature française; Marguerite Yourcenar; Mémoires d'Hadrien; Memories of Hadrien; roman historique; Yourcenar, Marguerite, 1903-1987; zgodovinski roman